Liver Transplantation for Hepatic Epithelioid Hemangioendothelioma: The Canadian Multicentre Experience. (2008) - Nudo, Carmine G; Yoshida, Eric M; Bain, Vincent G; Marleau, Denis; Wong, Phil; Marotta, Paul J; Renner, Eberhard; Watt, Kymberly D; Deschênes, Marc
Abstract : INTRODUCTION: Hepatic epithelioid hemangioendothelioma (HEHE) is a rare entity. At the present time, there is no standardized effective therapy. Liver transplantation (LT) has emerged as a treatment for this rare tumour. OBJECTIVE: To evaluate the outcome of liver transplantation for HEHE at eight centres across Canada. METHODS: The charts of patients who were transplanted for HEHE at eight centres across Canada were reviewed. RESULTS: A total of 11 individuals (eight women and three men) received a LT for HEHE. All LTs were performed between 1991 and 2005. The mean (± SD) age at LT was 38.7±13 years. One patient had one large liver lesion (17 cm × 14 cm × 13 cm), one had three lesions, one had four lesions and eight had extensive (five or more) liver lesions. One patient had spleen involvement and two had involved lymph nodes at the time of transplantation. The mean duration of follow-up was 78±63 months (median 81 months). Four patients (36.4%) developed recurrence of HEHE with a mean time to recurrence of 25±25 months (median 15.6 months) following LT. The calculated survival rate following LT for HEHE was 82% at five years. CONCLUSIONS: The results of LT for HEHE are encouraging, with a recurrence rate of 36.4% and a five-year survival rate of 82%. Further studies are needed to help identify patients who would benefit most from LT for this rare tumour.